Cour suprême, Cour d'arbitrage ou Cour constitutionnelle ? - Delpérée, Francis (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1985)
The comparative analysis of political societies can provide some models for those who are concerned with the reform of an institution. Three comparative models are presented here in the context of the discussion about the role and organization of the Supreme Court of Canada : the American model of a Supreme Court, the Belgian model of an Arbitration Court, and the German model of a Federal Constitutional Court. The different types of jurisdiction of these Courts as well as the different modes of designation of their members are discussed.